An analytical study of the plasticity of sandwich honeycomb panels subjected to low-velocity impact. (1st July 2019) - Sun, Mengqian; Wowk, Diane; Mechefske, Christopher; Kim, Il Yong
Abstract: A new analytical modelling method for the study of low-velocity impact response in honeycomb sandwich panels with metallic face-sheets is proposed by using Hamilton's principle. A modified Lagrange's function for this model is then proposed by extending the application of Hamilton's principle from elastic bodies to face-sheets with plasticity. The internal physical mechanism in the system is proved to be reasonable by comparing the energy converting history with published data. This study advances the understanding of the role of face-sheet plasticity in low-velocity impact response of honeycomb sandwich panels by having the ability to incorporate either the energy absorption from elastic deformation or the energy dissipation from plastic deformation of the face-sheet depending on the severity of the damage state in the dented region. The predicted maximum deflection and impact force history are compared with published experimental and finite element results, and lower and upper bounds of the maximum dent depth are obtained.